Kamsen Pilawong’s Teaching of Blow Khaen - Weangsamut, Rattasart (Journal of Music and Performing Arts Khon Kaen University, 2021)
This article presents information from studying the area of the Mekong cultural information study project at The National Art School, Lao People’s Democratic Republic of PhD students, Doctor of Philosophy Program in Music, Faculty of Fine and Applied Arts, Khon Kaen University. The purpose of this study was to learn the methods of teaching how to blow Khaen by Kamsen Pilawong. Who is the only khaen instructor that teaches students in first and second grade of The National Art School, Lao People’s Democratic Republic. Which is a compulsory subject for students to study and practice dioew khaen in total of 3 patterns, namely Phu Tom Dok pattern, Lom Phap Prao pattern and the Champa pattern of Laos These 3 monograms are regarded as the dioew Khaen patterns that are of great importance in the succession of Lao khaen playing. This article presents the preparation of Khamsen Pilawong’s teaching of blow Khaen, Implementation of Khamsen Pilawong’s blow Khaen teaching and an evaluation of Khamsen Pilawong’s blow Khaen teaching.